Poly(ethylene disulfide)/carbon fiber composites: cure and effect of fiber content on mechanical and thermal properties. (2nd November 2021) - Sheydaei, Milad; Edraki, Milad; Alinia-Ahandani, Ebrahim; Nezhadghaffar-Borhani, Erfan
Abstract : In this paper, poly(ethylene disulfide) (PEDS) and carbon fiber (CF) composites were synthesized using in situ polymerization. Then, synthesized composites, sulfur, zinc oxide (ZnO), stearic acid, and N -cyclohexyl-2-benzothiazole sulfenamide (CBS) were compounded using a two-roll mill and cured by a rheometer at 140°C. PEDS characteristics were investigated by Fourier transform infrared (FTIR), Raman spectroscopies, X-ray diffraction (XRD), proton nuclear magnetic resonance ( 1 H NMR), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). Also, cured samples were investigated by scanning electron microscopy (SEM), FTIR, Raman spectroscopies, XRD, DSC, and TGA. Moreover, the mechanical properties and hardness of the samples were investigated by tensile test and Shore A. The results showed that after the curing process, due to the cross-links, the structure is completely amorphous and no melting temperature ( T m ) has been observed. Also, by increasing CFs in composites, the glass transition temperature occurs at higher temperatures. Moreover, the thermal stability of composites by increasing CFs was enhanced. Furthermore, by an increase of CFs in matrix, hardness, and elastic modulus, as well as strength, were increasing. GRAPHICAL ABSTRACT: UF0001